Nitrogen and Organic Carbon Removal from Landfill Leachate under Feammox Conditions - Dang Luu, Nguyen; Anh Huyen, Nguyen; Thi Hoanh Oanh, Le; Thuy Hang, Dinh; Thi Hai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3, 2023)
Wastewater with high ammonium (NH 4 + ) content and low carbon-to-nitrogen (C/N) ratios is challenging for treatment technologies. The currently applied nitrogen removal technologies, including: i) Nitrification-denitrification; and ii) Partial nitritation-anammox, are insufficient for wide application. The nitrification-denitrification technology is costly due to the high oxygen demand (for the nitrification step) and the requirement for additional organic carbon (for the denitrification step). Meanwhile, the partial nitritation-anammox technology requires a stable NH 4 + /NO 2 − ratio, whereas the wastewater composition often fluctuates. Feammox is an anaerobic respiration pathway discovered at the beginning of the 21 st century and has recently been shown applicable in the removal of nitrogen and organic carbon simultaneously with the advantages of energy saving and simplicity in operation. In this study, a lab-scale Feammox procedure was performed to remove nitrogen and organic carbon from mature landfill leachate with extremely high NH 4 + and COD contents, and very low C/N and BOD/COD ratios. The results showed that the highest removal efficiencies for NH 4 + (90%) and COD (63%) were achieved at a C/N ratio of 1.8 with the initial NH 4 + concentration of 100 mg/L and a hydraulic retention time of 6 days. Increasing the C/N ratio of wastewater to 2.5 led to an increase in COD removal efficiency to 80%, however, it reduced the NH 4 + removal efficiency to 58%. The NH 4 + treatment efficiency was also decreased to 58% when the initial NH 4 + concentration was increased to 150 mg/L, even if the hydraulic retention time was extended to 8 days. These results showed that nitrogen and carbon co-removal from diluted landfill leachate could be efficiently achieved via the Feammox process.